Tracking the reading eye: towards a model of real‐world reading. (June 2017) - Jarodzka, H.; Brand‐Gruwel, S.
Abstract: Eye tracking has helped to understand the process of reading a word or a sentence, and this research has been very fruitful over the past decades. However, everyday real‐world reading dramatically differs from this scenario: we read a newspaper on the bus, surf the Internet for movie reviews or browse folders at work to fill in forms. Therefore, we propose to structure eye‐tracking research in reading into three levels of reading: level 1 research on reading to investigate single words or sentences, level 2 research on reading and comprehending a whole text and level 3 research on reading and processing involving several text documents. The present Special Section includes three articles investigating real‐world reading on levels 2 and 3. These articles show how real‐world reading can be investigated by means of eye tracking and complementary methods, to understand how we read, comprehend and integrate texts in realistic, everyday scenarios. Such new research lines broaden our knowledge of reading itself. Lay Description: What is already known about this topic: Students with good reading comprehension skills can identify and deeply process hypertext sections relevant for their goal more efficiently than poor comprehenders. Poor comprehenders tend to quickly scan hypertext sections without noticing the relevant information they encounter. What this paper adds: Scanning relevant hypertext sections is related to lower performance, especially for good comprehenders. Deep processing of relevant hypertext sections is positively related to better performance, independent of reading comprehension skills. Implications for practice and/or policy: All students, independent of their reading comprehension skills, must be taught not to overuse scanning of hypertext sections. Another beneficial strategy is to use contextual cues (e.g., section headings) to predict relevance of a hypertext section.